An unusual combined thymic carcinoma composed of squamous cell carcinoma and type AB thymoma: a rare case report. Issue 1 (December 2017) - Jiang, Yufeng; Liu, Yang; Shi, Xiuying; Mao, Xiaoyun; Zhao, Yang; Fan, Chuifeng
Abstract Background Combined thymic carcinoma is a malignant neoplasm of the thymus recently added to the 4th edition of the World Health Organization (WHO) classification of tumors of the lung, pleura, thymus and heart. It involves at least one type of thymic carcinoma and another thymic epithelial tumor. The previously used term "combined thymic epithelial tumor" has been abandoned. Case presentation Here, we present an unusual case of combined thymic carcinoma of the thymus in a 44-year-old male who had suffered from fever, chest pain, chest tightness and shortness of breath. Magnetic resonance imaging (MRI) detected a mass approximately 6.4 cm × 4.2 cm in the anterior mediastinum, and a nonencapsulated tumor approximately 5.0 cm × 3.5 cm × 2.5 cm with an irregular shape was resected. The morphological features and the immunostaining pattern of the tumor revealed it to be an unusual combined thymic carcinoma consisting of type AB thymoma and squamous cell carcinoma. There were cysts of various sizes, some of which had crack-like structures, in the type AB thymoma area. A gradual transition could be seen between these structures and the squamous cell carcinoma, indicating that the carcinoma portion may have originated from the composition of the thymoma. Conclusions Combined thymic carcinoma composed of type AB thymoma and squamous cell carcinoma is rare, and the carcinoma portion may have originated from epithelial structures in the type AB thymoma.